Brief Communication: Histological Assessment of Nonhuman Primate Brown Adipose Tissue Highlights the Importance of Sympathetic Innervation - Abigail G. Williams; Masha Long; Kylie Kavanagh (Journal of Obesity)
Objective. The objective of this study was to functionally analyze the correlation of key histological features in brown adipose tissue (BAT) with clinical metabolic traits in nonhuman primates. Methods. Axillary adipose tissue biopsies were collected from a metabolically diverse nonhuman primate cohort with clinical metabolism-related data. Expression of tyrosine hydroxylase (TH), uncoupling protein 1 (UCP1), cluster of differentiation 31 (CD31), cytochrome c oxidase subunit 4 (COX IV), beta-3 adrenergic receptor (β3-AR), and adipose cell size were quantified by immunohistochemical analysis. Computed tomography scans were performed to assess body composition. Results. Tyrosine hydroxylase was negatively correlated with whole body fat mass as a percentage of body weight (p = 0.004) and was positively correlated with the density of UCP1 (p = 0.02), COX IV (p = 0.006), CD31 (p = 0.007), and cell density (p = 0.02) of the BAT samples. Beta-3 adrenergic receptor abundance had a weak positive correlation with COX IV (p = 0.04) in BAT but did not significantly correlate to UCP1 or TH expression in BAT. Conclusions. Our findings highlight that there is a disparity in innervation provided to BAT based on body composition, as seen with the negative association between TH, a marker for innervation, and adiposity. These findings also support the importance of innervation in the functionality of BAT, as TH abundance not only supports leaner body composition but is also positively correlated with known structural elements in BAT (UCP1, COX IV, CD31, and cell density). Based on our observations, β3-AR abundance does not strongly drive these structural elements or TH, all of which are known to be important in the function of brown adipose tissue. In effect, while the role of other receptors, such as β2-AR, should be reviewed in BAT function, these results support the development of safe sympathetic nervous system stimulants to activate brown adipose tissue for obesity treatment.